Drug policies and development : conflict and coexistence - Buxton, Julia (International development policy,, 2020)
"The 12th volume of International Development Policy explores the relationship between international drug policy and development goals, both current and within a historical perspective. Contributions address the drugs and development nexus from a range of critical viewpoints, highlighting gaps and contradictions, as well as exploring strategies and opportunities for enhanced linkages between drug control and development programming. Criminalisation and coercive law enforcement-based responses in international and national level drug control are shown to undermine peace, security and development objectives. Contributors include: Kenza Afsahi, Damon Barrett, David Bewley-Taylor, Daniel Brombacher, Julia Buxton, Mary Chinery-Hesse, John Collins, Joanne Csete, Sarah David, Ann Fordham, Corina Giacomello, Martin Jelsma, Sylvia Kay, Diederik Lohman, David Mansfield, José Ramos-Horta, Tuesday Reitano, Andrew Scheibe, Shaun Shelly, Khalid Tinasti, and Anna Versfeld"--